PENGGUNAAN MEDIA DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Afriani, Yulia; Dinova, Ardilla; Rahmawati, Elsa; Winingsi, Kartika Rama; Agustin, Lystiya; Yunita, Mila; Putri, Oriza Sativa; Nurhasanah, Siti; Amalia, Via; Yolanda, Fitriana (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2024)
It takes people who have an understanding of education to manage education. The educational process cannot be separated from human resource development. Education is an indicator of someone's quality. Apart from that, the media has an important role in education. The process of conveying a message from the message source to the message recipient through certain media is called communication, and occurs during the teaching and learning process. There are four main objectives of learning media, namely cognitive, emotive, attentional and compensatory. To improve learning outcomes and efficiency, educational media can also help in fostering relationships between teachers and students. The aim of this research is to describe how important it is for teachers to use learning media in mathematics. This research is a qualitative descriptive study. The research results show that it will be easier for teachers to teach and learn if they use learning media.